2011
DOI: 10.19030/iber.v7i6.3264
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Distinctive Capabilities And The Performance Of Small And Medium-Size Enterprises (SMES) In Malaysia

Abstract: This study analyzes strategic factors that can influence the performance of small and medium size enterprises (SMEs) in the Malaysian manufacturing sector. The conceptual framework is developed based on the distinctive capabilities and the performance of the SMEs. This study is based on a sample survey of 121 SMEs in the manufacturing sector. Using structured questionnaires, the data is collected by mailing as well as interviews with owner-managers of the SMEs. Using the Statistical Package of Science Social (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The R2 (coefficient of determination) of distinctive capabilities indicated 40.8% of the level of competitive advantage rattan furniture industry Cirebon. These findings appear consistent with the study conduct by Man and Wafa indicated has a significant correlation between distinctive capabilities and performance of SMEs or competitive advantage [15]. According Jackson, with distinctive capabilities the organization more friendliness than others for employees, supplier, and also the competitors [6].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The R2 (coefficient of determination) of distinctive capabilities indicated 40.8% of the level of competitive advantage rattan furniture industry Cirebon. These findings appear consistent with the study conduct by Man and Wafa indicated has a significant correlation between distinctive capabilities and performance of SMEs or competitive advantage [15]. According Jackson, with distinctive capabilities the organization more friendliness than others for employees, supplier, and also the competitors [6].…”
Section: Resultssupporting
confidence: 88%
“…But have the different indicator to measure distinctive capabilities. Several previous studies revealed that is a significant correlation between distinctive capabilities and performance of SMEs or competitive advantage, and indicators of distinctive capabilities based on Hitt and Ireland grouped according to seven functional areas [14] (1) general administration, (2) production/operation, (3) engineering, research, and development, (4) marketing, (5) finance, (6) personal, (7) public and governmental relatins [15]. The result indicates all performance SMEs indicators could be explained by the distinctive capabilities and average equity performance got the highest correlation by 64.4%.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The question items were developed after a thorough review of literature related on intellectual capital and performance such as Atieno (2009), Man and Wafa (2008), Boudreau and Ramstad, (1997), Marr and Neely (2001). In this study the scales for business strategies (Croteau ve Bergeron, 2001) were used.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Hence family support is a key factor in managing their business successfully. Financial capability is the ability to manage the finances and use financial services in th most appropriate manner to meet the needs and the prevalent social and economic situations (Man, & Wafa, 2008). Many factors affect the financial capabilities.…”
Section: The Conceptual Modelmentioning
confidence: 99%